FPGA based early fault detection system - Aydin, Ilhan; Karaköse, Mehmet; Akin, Erhan (My University, 2010)
In this study, an FPGA based method has been presented for detection of broken rotor bar faults occurred in induction motors. The proposed method takes one phase current signal and extracts feature signal by applying Hilbert transform. Each state of finite state machine is obtained calculating the entropy value on feature signal. The state transition matrix is constructed in real time on FPGA environment. The diagonal elements of this matrix are compared to a threshold value and faults are detected. The proposed method was confirmed by implementing on Altera Cyclone III FPGA card and MATLAB environment.
FPGA tabanli erken ariza tespit sistemi
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- 2 December 2010 through 5 December 2010 -- Bursa -- 83834
Keywords: Electrical engineering; Fault detection; Induction motors; Storms; Altera cyclones; Broken rotor bar fault; Diagonal elements; Early fault; Entropy value; Finite state machines; Hilbert transform; MATLAB environment; matrix; Phase currents; Real time; State transition Matrix; Signal detection